Promoting Attitudes Towards Disability in University Settings: A Quasi-Experimental Study - Luisa Gámez-Calvo; Margarita Gozalo; Miguel A. Hernández-Mocholí; Jesús Muñoz-Jiménez (European Journal of Investigation in Health, Psychology and Education)
Inclusive Education emphasizes equal opportunities for all students by reducing or eliminating barriers that hinder participation and learning, encompassing cultural, social, practical, and political dimensions. In this context, the development of positive attitudes towards disability is a key component for the success of inclusive educational practices, particularly in adapted physical education. Following a prior analysis of the impact of academic curricula on attitudes toward disability, the need to implement training programs focused on attitudes toward disability becomes evident. The aim of this study is to analyze how a training program, with a specific focus on attitudes toward disability, affect the attitudes among university students. A quasi-experimental approach with a control group was employed to evaluate the impact of the training. A total of 137 University students from Extremadura, across Physical Activity and Sport Science and Early Childhood Education programs within the same educational department, participated in this study. The Spanish Attitudes Toward People with Disabilities Scale for Professionals was administered to students at the beginning, after the theoretical intervention, and after having a guided contact with people with disability. Results revealed improvements in attitudes in the social relationships and normalized life dimensions, as well as in the total score, particularly among students from Early Childhood Education. No significant changes were observed in the intervention program dimension. Within-group analysis indicated significant longitudinal improvements in normalized life for both experimental groups, Sports Science and Early Childhood Education students, and in the total score for Early Childhood Education students by the end of the intervention. These findings highlight the importance of targeted training interventions in promoting inclusive attitudes, especially when direct contact with individuals with disabilities is incorporated.